1991
DOI: 10.1093/infdis/164.4.741
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis Facilitated by Murine Retroviral Infection with LP-BM5

Abstract: LP-BM5 murine leukemia virus infection caused alterations in splenic T cell subsets in adult C57BL/6 female mice. Prolonged infection resulted in increased immunosuppression and a concomitant decreased resistance to Cryptosporidium parvum infection. Significant Cryptosporidium colonization of the intestinal villi was seen 10 days after oral challenge in mice infected with murine retrovirus for 3 months but not in non-virally infected controls. Parasite numbers per villus of retrovirally infected mice were 20-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that a lack of coordinated responses from CD8 + T-cells and natural killer cells facilitated HSV-1 spread into brains of C57BL/6 mice [31]. MAIDS models have been extensively used to understand the pathogenesis of opportunistic infections [18,20,21,32]. In our model of LP-BM5-induced immunodeficiency, otherwise resistant C57BL/6 mice became sensitive to opportunistic brain infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that a lack of coordinated responses from CD8 + T-cells and natural killer cells facilitated HSV-1 spread into brains of C57BL/6 mice [31]. MAIDS models have been extensively used to understand the pathogenesis of opportunistic infections [18,20,21,32]. In our model of LP-BM5-induced immunodeficiency, otherwise resistant C57BL/6 mice became sensitive to opportunistic brain infection.…”
Section: Discussionmentioning
confidence: 93%
“…It has been postulated that this Th1 to Th2 shift is required for progression to MAIDS. Furthermore, this retroviral infection increases susceptibility to other infections and has been used to study opportunistic parasites and fungi [19-21]. Normal C57BL/6 mice have been shown to be resistant to HSV-1 encephalitis when inoculated through the i.n.…”
Section: Resultsmentioning
confidence: 99%
“…Prior infection of C57BV6 mice with LP-BMS MuLVs did not affect the kinetics of C. neoformans infection, as fungal counts in the lungs and brain remained similar in LP-BMS-infected and MuLV induces profound immunodeficiency. It has been shown that the immune defects occurring during this retroviral disease increase susceptibility to various pathogens [ 16, including a fungus. Cole et al reported increased susceptibility to gastrointestinal candidiasis after LP-BMS-induced immunosuppression [17].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that retrovirus-infected mice could become infected with Cryptosporidium parvum a gut parasite, was a starting point for an interest in how LP-BM5 infection was altering gut mucosal immunity (Darban et al 1991). Further studies clearly indicated that while mesenteric lymph nodes (MLN) increased in size and cell numbers the opposite was the case for Peyer's patches and the gut lamina propria (Lopez et al 1992c).…”
Section: Introductionmentioning
confidence: 99%